Towards Designing A Model For Evaluation Of Business Critical Software Systems: A Tool For Software Procurement - Ashenafi, Duguma (ASTU, 2016)
The process of purchasing commercial software system needs systematic guidelines; so that the appropriate software system can be selected in order to provide a feasible and effective solution to the organizations. However, more of the existing evaluation and selection system for commercial software system focus more on functional characteristics of the system and do not give that much attention to nonfunctional characteristics of the system and to the mismatch between the user requirement and the desired software system. This study aimed to design evaluation model for business critical software system that focus on handling functional and nonfunctional feature of system and the mismatch with the expected characteristics of the desired software system. The study is conducted using the methodology which involves interview, questionnaire and literatures. Analytical hierarchical processing decision making technique is used for the evaluation process, handling of software mismatch and validating the model. The major results of the study are identifying common business software evaluation criteria attributes and evaluation process used to select the desired software system. The result shows that evaluation aspects of the model is feasible and demonstrate the potential of the system and practicality where it could be applied to the actual environment. Contribution of this study for the research and practical perspectives of software evaluation and selection would improve the decision making and providing systematic guidelines for handling issue in purchasing commercial software.
Keywords: Software evaluation, Software selection, Analytical Hierarchical Processing (AHP), Commercial off-the-shelf (COTS)